Flash pyrolysis of silicon-bound hydrocarbons - Sinninghe Damsté, J.S.; Hartgers, W.A.; Leeuw, J.W. de (Elsevier, 1991)
Curie-point flash pyrolysis-gas chromatography/mass spectrometry of n-octadecane, n-propylbenzene and n-propylcyclohexane chemically linked to silica has been performed in order to gain a better understanding of the mechanism of flash pyrolysis by which hydrocarbons are generated from kerogens. The major products result via a 6-membered ring rearrangement involving the Si---O---C linkage and from cleavage of C---C bonds allylic to primary or secondary alkyl radicals
Keywords: Aardwetenschappen